PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SISTEM OFF-GRID SEBAGAI SUPLAI DAYA LISTRIK PADA GEDUNG KANTOR KEJAKSAAN NEGERI REJANG LEBONG - Mauriska Khoirotunnisa; Haris Gunawan; Siti Anisah (Jurnal Nasional Teknologi Komputer, 2026)
The Rejang Lebong District Attorney's Office building requires a reliable electricity supply to support its operational activities and public services, while its electricity consumption continues to rise each year. The use of an off-grid solar power plant (PLTS) serves as a strategic solution to reduce dependence on conventional electricity while supporting the government's clean energy transition program. This study employs a quantitative method with a technical design approach based on electricity consumption data, solar radiation potential of 4,536 kWh/m2/day, and average temperature data for the Rejang Lebong region. The planning results indicate a daily energy requirement of 286.22 kWh/day, met by 120 units of LR5-72HPH 550 Wp monocrystalline solar panels (66.05 kWp), 6 units of Sungrow SH15T hybrid inverters, and 79 units of 96V 100Ah LiFePO4 batteries with a 2-day autonomy. The initial investment for the system is Rp 4,149,000,000, with electricity bill savings of Rp 177,553,795 per year and net savings of Rp 136.063.795 per year after deducting operational and maintenance costs.